Islam, Religion, Practice, Culture and World Order: By Imtiyaz Yusuf, ed. (Herndon, VA: The International Institute of Islamic Thought, 2012. 96 pages.) (American Journal of Islam and Society, 2013)
Isma‘il al-Faruqi (1921-86), a reformer, a visionary, and a great modernscholar, wrote on several aspects of Islam and Muslim interactions with majorspiritual traditions of the world. This short book is a collection of his brief reflectionson Islam’s basic ideals. Thus it is not a research work, but rather anexplication on how Islam should be comprehended on its own merit. Expressedin simple language to make its contents accessible to the general publicand containing no references, it consists of seven parts each comprised ofthree or four chapters. The arrangement of topics was not chronological, eventhough one would have expected its editor, Imtiyaz Yusuf – one of al-Faruqi’sstudents – to pay attention to such order by rearranging the chapters. For example, one would logically expect the discussion of the isrOE’ and mi‘rOEj tocome before the discussion of the hijrah ...